Key Ethical Issues Discussed at CDC-Sponsored International, Regional Meetings to Explore Cultural Perspectives and Contexts on Pandemic Influenza Preparedness and Response - Aun Lor; James C. Thomas; Drue H. Barrett; Leonard W. Ortmann; Dionisio J. Herrera Guibert (Kerman University of Medical Sciences, 2016)
Background Recognizing the importance of having a broad exploration of how cultural perspectives may shape thinking about ethical considerations, the Centers for Disease Control and Prevention (CDC) funded four regional meetings in Africa, Asia, Latin America, and the Eastern Mediterranean to explore these perspectives relevant to pandemic influenza preparedness and response. The meetings were attended by 168 health professionals, scientists, academics, ethicists, religious leaders, and other community members representing 40 countries in these regions. Methods We reviewed the meeting reports, notes and stories and mapped outcomes to the key ethical challenges for pandemic influenza response described in the World Health Organization's (WHO's) guidance, Ethical Considerations in Developing a Public Health Response to Pandemic Influenza: transparency and public engagement, allocation of resources, social distancing, obligations to and of healthcare workers, and international collaboration. Results The important role of transparency and public engagement were widely accepted among participants. However, there was general agreement that no "one size fits all" approach to allocating resources can address the variety of economic, cultural and other contextual factors that must be taken into account. The importance of social distancing as a tool to limit disease transmission was also recognized, but the difficulties associated with this measure were acknowledged. There was agreement that healthcare workers often have competing obligations and that government has a responsibility to assist healthcare workers in doing their job by providing appropriate training and equipment. Finally, there was agreement about the importance of international collaboration for combating global health threats. Conclusion Although some cultural differences in the values that frame pandemic preparedness and response efforts were observed, participants generally agreed on the key ethical principles discussed in the WHO's guidance. Most significantly the input gathered from these regional meetings pointed to the important role that procedural ethics can play in bringing people and countries together to respond to the shared health threat posed by a pandemic influenza despite the existence of cultural differences.